A STUDY TO INVESTIGATE FACTORS INFLUENCING CAREER CHOICE AMONG UNDERGRADUATE STUDENTS: A CASE STUDY IN UITM SEREMBAN - Nurul Batrisyia Norahim; Nor Hidayah Hassim; Siti Hasma Hajar Mat Zin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Career choices significantly impact students' futures, yet many struggle to make wise decisions. Students often base their employment decisions on a range of factors that shape their lives. This study investigates factors influencing career choices among undergraduate students in UiTM Seremban. The research objectives were to: (1) identify the preferences for career types across different faculties, (2) determine the relationship between factors influencing career choice and (3) identify the most significant factor influencing career choices. Through convenience sampling, an online questionnaire was distributed to a sample of 361 students. The collected data were analysed using Multiple Linear Regression analysis with factors of Family Influence, Economic Considerations, Personal Interests and Self-Efficacy. The Multiple Bar Chart showed that students from the College of Computing, Informatics, and Mathematics (KPPIM) favoured jobs in the private sector, students from the Faculty of Sport Science and Recreation (FSR) showed the highest preference for government sector employment, and self-employment was mostly preferred by students from Faculty of Administrative Science and Policy Studies (FSPPP). Furthermore, the F-test demonstrated that all four factors significantly influence career choices. In contrast to other factors, personal interests appeared to be the only insignificant variable. Moreover, the t-test analysis resolved the most important factor influencing career choices was family influence. The results revealed the importance of addressing family influence and other factors to better match students' career choices with their goals and available market opportunities. Nevertheless, future research could benefit from recruiting probability sampling techniques such as stratified sampling, as well as incorporating other relevant variables like peer influence, starting salary, and job security. Overall, this research contributes to understanding how to improve career satisfaction and reduce youth unemployment by guiding students towards informed and fulfilling career paths.